ISSUES OF IMPROVEMENT OF ADMINISTRATIVE JUSTICE IN THE REPUBLIC OF UZBEKISTAN: NATIONAL AND FOREIGN PRACTICE - Raxmatillaevich, Artiqov Dilmurod (International Journal of Psychosocial Rehabilitation, 2020)
Administrative disputes arising in the relations of public administration between administrative body and the person are common in every state of the world. The administrative dispute resolution system is known as the "Administrative Justices" in theoretical and legal documents. However, the system of administrative justices has its own peculiarities in each country. Prompt, transparent and open implementation of the system serves to promote human rights in that country. Corruption that is rampant in some countries today can be prevented as a result of the perfect implementation of this system.